Determination of Phenolic and Flavonoid Total Levels and Antioxidant Activity of Ethanol, Ethyl Acetate, and n-Hexane Extracts of Citrus reticulata Blanco Fruit Peel by DPPH and ABTS Methods: Penetapan Kadar Total Fenol dan Flavonoid serta Aktivitas Antioksidan Ekstrak Etanol, Etil Asetat, dan n-Heksan Kulit Buah Citrus reticulata Blanco dengan Metode DPPH dan ABTS - Fadhlillah, Faizah Min; Miranti, Mila; Wibowo, Diki Prayugo; Purkon, Dicki Bakhtiar (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2024)
Background: The peel of the fruit Citrus reticulata Blanco has long been used in traditional medicine due to its various properties. Traditional medicine from certain parts of medicinal plants is related to the content of bioactive compounds from the fruit's peel, such as phenolic compounds and flavonoids that can help protect the body from damage caused by free radicals. Objectives: This study aimed to evaluate the total levels of phenolics and flavonoids as well as antioxidants from ethanol, ethyl acetate, and n-hexane extracts from the skin of Citrus reticulata Blanco using DPPH (2,2-diphenyl-1-picrylhydrazil) and ABTS (2,2'-azinobis-(3-ethylbenzothiazolin-6-sulphonate))) methods. Material and Methods: The extraction process was carried out using the maceration ion method with ethanol, ethyl acetate, and n-hexane solvents at room temperature for 24 hours. Total phenolic and flavonoid levels in the extract were determined using UV-Vis spectrophotometry, and antioxidant activity testing was determined based on the extract's ability to neutralize free radicals from DPPH and ABTS. Results: The results showed that the ethanol extract of Citrus reticulata Blanco fruit peel had higher total phenolic and flavonoid levels compared to ethyl acetate and n-hexane extracts. The total phenolic levels in ethanol, ethyl acetate, and n-hexane extracts were 142.02, 74.60, and 57.17 mg GAE/g, respectively. The total flavonoid levels in ethanol, ethyl acetate, and n-hexane extracts were 45.96, 40.22, and 38.54 mg QE/g, respectively. In addition, ethanol extract has also shown the strongest antioxidant activity based on the results of testing with DPPH and ABTS methods. The inhibitory concentration (IC50) of ethanol extract against DPPH and ABTS methods was 23,490 Î¼g/mL and 31,971 Î¼g/mL, respectively, with strong category. Conclusions: This study shows that the skin of Citrus reticulata Blanco fruit contains phenolic compounds and flavonoids that have the potential as natural antioxidants, with ethanol extract being the most promising related to total phenolic and flavonoid levels and antioxidant activity. This information can be used as a basis for developing pharmaceutical dosage products and health supplements that can potentially improve antioxidant/health status in the body.